FAKTOR-FAKTOR YANG MEMPENGARUHI KECURANGAN LAPORAN KEUANGAN DENGAN ANALISIS FRAUD TRIANGLE - Nurul Hafizah; Novita Weningtyas Respati; Chairina Chairina (Universitas Muhammadiyah Malang, 2017)
This research aims to examine, analyze, and obtain evidence the influences factors in fraudtriangle to financial statement fraud on Manufacturing Companies that Listed on IndonesiaStock Exchange. This research’s population are Manufacturing Companies that Listed on Indonesia Stock Exchange Period 2011-2015. In this research using purposive sampling method todetermine the samples. Total sample of this research are 57 companies. This research useslogistic regression analysis to examine the effects of various independent variables on financialstatement fraud. The independent variables in this research are factors in fraud triangle. Theresult of this research indicated that financial stability influences the financial statementfraud. However, other variabel like external pressure, personal financial need, financial targets,nature of the industry, effective monitoring, and rationalization were not influence on financialstatement fraud.Keywords: Financial statement fraud, fraud triangle, pressure, opportunity, rationalization